TELAAH EMPIRIS FAKTOR-FAKTOR PENENTU PENERIMAAN PAJAK - Fransiska Laelatul Luviana; Ardiani Ika Sulistyawati (JURNAL LENTERA AKUNTANSI, 2022)
This study aims to empirically examine the effect of NPWP ownership obligations, tax audits, tax collection, and taxpayer awareness on tax revenues at the KPP Pratama Demak tax office. The population of this research is all taxpayers.  In this research, purposive sampling technique is used. The sample used in this study were 96 respondents. The results of this study indicate that all independent variables, namely NPWP ownership obligation, tax audit, tax collection, and taxpayer awareness have a positive and significant effect on tax revenue (Y) partially or simultaneously (together). Based on the coefficient of determination of 0.929. In this case, it means 92.9% of purchasing decision variables. It is explained by the variable of NPWP ownership, tax audit, tax collection, taxpayer awareness of tax revenue. While the remaining 7.1% is explained by other variables outside the model.Key words : Taxpayer Identification Number Obligation, Tax Audit, Tax Collection, Taxpayer Awareness and Tax Revenue